ASP.NET Web API 2: Building a REST Service from Start to Finish - Kurtz, Jamie (Apress, 2014)
The ASP.NET MVC Framework has always been a good platform on which to implement REST-based services, but the introduction of the ASP.NET Web API Framework raised the bar to a whole new level. Now in release version 2.1, the Web API Framework has evolved into a powerful and refreshingly usable platform. This concise book provides technical background and guidance that will enable you to best use the ASP.NET Web API 2 Framework to build world-class REST services. New content in this edition includes: • New capabilities in Web API 2 (currently version 2.1). • Support for partial updates, or PATCH. • API versioning. • Support for legacy SOAP-based operations. • How to handle non-resource APIs using REST • How to best expose relationships between resources • JSON Web Tokens, CORS, CSRF Get ready for authors Jamie Kurtz and Brian Wortman to take you from zero to REST service hero in no time at all. No prior experience with ASP.NET Web API is required; all Web API-related concepts are introduced from basic principles and developed to the point where you can use them in a production system. A good working knowledge of C# and the .NET Framework are the only prerequisites to best benefit from this book.